Negative cancer stereotypes and disease‐specific self‐concept in head and neck cancer. Issue 5 (13th June 2012) - Wong, Janice C.; Payne, Ada Y. M.; Mah, Kenneth; Lebel, Sophie; Lee, Ruth N. F.; Irish, Jonathan; Rodin, Gary; Devins, Gerald M.
Abstract Background Life‐threatening diseases, such as head and neck cancer (HNCa), can stimulate the emergence of a new disease‐specific self‐concept. We hypothesized that (i) negative cancer‐stereotypes invoke distancing, which inhibits the adoption of a disease‐specific self‐concept and (ii) patient characteristics, disease and treatment factors, and cancer‐related stressors moderate the phenomenon. Methods Head and neck cancer outpatients (N = 522) completed a semantic‐differential measure of disease‐specific self‐concept (perceived similarity to the 'cancer patient') and other self‐report measures in structured interviews. Negative cancer‐stereotypes were represented by the number of semantic‐differential dimensions (0–3) along which respondents evaluated the stereotypic 'cancer patient' negatively (i.e., negative valence). We tested the two‐way interactions between negative valence and hypothesized moderator variables. Results We observed significant negative valence × moderator interactions for the following: (i) patient characteristics (education, employment, social networks); (ii) disease and treatment factors (cancer‐symptom burden); and (iii) cancer‐related stressors (uncertainty, lack of information, and existential threats). Negative cancer stereotypes were consistently associated with distancing of self from the stereotypic 'cancer patient, ' but the effect varied across moderator variables. All significant moderators (except employment and social networks) were associated with increasing perceived similarity to the 'cancer patient' when respondents maintained negative stereotypes; perceived similarity decreased when people were employed or had extensive social networks. Moderator effects were less pronounced when respondents did not endorse negative cancer stereotypes. Discussion When they hold negative stereotypes, people with HNCa distance themselves from a 'cancer patient' identity to preserve self‐esteem or social status, but exposure to cancer‐related stressors and adaptive demands may attenuate these effects. Copyright © 2012 John Wiley & Sons, Ltd.